The PI3k/Akt pathway is associated with angiogenesis, oxidative stress and survival of mesenchymal stem cells in pathophysiologic condition in ischemia - Samakova, A; Gazova, A; Sabova, N; Valaskova, S; Jurikova, M; Kyselovic, J (Physiological research, 2019)
Ischemic diseases are characterized by reduced blood supply to a tissue or an organ due to obstruction of blood vessels. The most serious and most common ischemic diseases include ischemic heart disease, ischemic stroke, and critical limb ischemia. Revascularization is the first choice of therapy, but the cell therapy is being introduced as a possible way of treatment for no-option patients. One of the possibilities of cell therapy is the use of mesenchymal stem cells (MSCs). MSCs are easily isolated from bone marrow and can be defined as non-hematopoietic multipotent adult stem cells population with a defined capacity for self-renewal and differentiation into cell types of all three germ layers depending on their origin. Since 1974, when Friedenstein and coworkers (Friedenstein et al. 1974) first time isolated and characterized MSCs, MSC-based therapy has been shown to be safe and effective. Nevertheless, many scientists and clinical researchers want to improve the success of MSCs in regenerative therapy. The secret of successful cell therapy may lie, along with the homing, in secretion of biologically active molecules including cytokines, growth factors, and chemokines known as MSCs secretome. One of the intracellular signalling mechanism includes the activity of phosphatidylinositol-3-kinase (phosphoinositide 3-kinase) (PI3K) - protein kinase B (serine-threonine protein kinase Akt) (Akt) pathway. This PI3K/Akt pathway plays key roles in many cell types in regulating cell proliferation, differentiation, apoptosis, and migration. Pre-conditioning of MSCs could improve efficacy of signalling mechanism.
Keywords: Proto-Oncogene Proteins c-akt; Mesenchymal Stem Cell Transplantation; Ischemia; Neovascularization, Physiologic; Oxidative Stress; Mesenchymal Stem Cells; Phosphatidylinositol 3-Kinases; transplantace mezenchymálních kmenových buněk; fyziologická neovaskularizace; ischemie; fosfatidylinositol-3-kinasy; protoonkogenní proteiny c-akt; rho-Associated Kinases; mezenchymální kmenové buňky; kinázy asociované s Rho; zvířata; Humans; oxid dusnatý; Nitric Oxide; oxidační stres; lidé; Animals